CABLE VERSUS SHOCK‐CORD HARNESSES: EFFECTS ON FEMALE WILD TURKEY MORTALITY - Steven D. Roberts; William F. Porter (Wildlife Society Bulletin)
Abstract: A major assumption inherent to survival studies is that radio‐tagging does not affect the survival of individuals. If biologists arbitrarily accept this assumption to be true, negatively biased survival rates could result. We obtained survival data from female eastern wild turkeys (Meleagris gallopavo silvestris) in south‐central New York during 1990‐91 to determine whether survival differences existed between hens equipped with either shock‐cord or aircraft‐cable harnesses. Postcapture (28 days after instrumentation) survival of cable‐harnessed hens (S = 0.757, SE = 0.071, n = 37) was lower (P = 0.005) than that of shock‐cord‐harnessed hens (S = 0.966, SE = 0.023, n = 61). Although confounding factors prevented direct conclusions, ancillary data suggested that cable harnesses may negatively affect postcapture survival. Annual survival of cable‐harnessed hens (S = 0.387, SE = 0.098, n = 28) was marginally lower (P = 0.10) than that of shock‐cord‐harnessed hens (S = 0.640, SE = 0.119, n = 20). More similar (P = 0.26) survival rates were observed when harness‐related mortalities were censored. Use of cable harnesses could negatively affect wild turkey survival.